Edukasi Obat Tradisional dan Penyakit Diabetes Mellitus serta Hipertensi untuk Masyarakat Sidrap - Abidin, Hamdayani Lance; Hapiwaty, Saldi; Ali, Alimuddin; Ningsih, Ririn Iriani; Tandiarrang, Lira; Hendrarti, Wahyu; Amin, Astuti (Penerbit Goodwood, 2025)
Purpose: The purpose of the Arga Math program is to introduce and implement the “Plakat” (Rank Number Board) as an innovative teaching aid to enhance students’ mathematical understanding, specifically in exponentiation. This visual tool aims to foster student engagement, simplify abstract concepts, and support teachers in creating more interactive and effective learning environments. Methodology/approach: The socialization activity was conducted at MTS Sinoa using a service-learning approach focused on knowledge transfer. The session began with a brief presentation on the concept and function of Plakat Teaching Aid. This was followed by hands-on practice, where participants applied the tool to solve exponent-related problems. Feedback and perceptions were collected through a structured questionnaire completed by teachers and students after the activity. Results/findings: The results of the activity showed that the Plakat teaching aid helped both teachers and students better understand exponentiation. Students demonstrated increased enthusiasm and confidence in solving exponential problems, while teachers acknowledged the usefulness of the tool in delivering abstract content. Furthermore, the activity motivated educators to design similar instructional media that aligned with curriculum objectives and encouraged creativity in teaching mathematics. Conclusions: The Arga Math Plakat proved to be an effective visual learning aid, making abstract mathematical concepts more accessible. It positively affects learning outcomes and inspires both students and educators. Limitations: The activity had limited reach due to time constraints and the participation of only 13 eighth-grade students, with minimal involvement from other educators. Contribution: This initiative supports educational innovation and contributes to achieving SDG Goal 4: Quality Education.